Enhancing Nursing Care through Electronic-Based Handover in Hospital Settings: A Systematic Review - Enniq Mazayudha; Daviq Ayatulloh; Diah Priyantini; Nursalam Nursalam (Universitas Airlangga, 2026)
Introduction: Handover is a critical nursing responsibility involving the structured transfer of essential patient information, accountability, and continuity of care between healthcare providers. In nursing practice, ineffective or unstructured handover communication has been consistently associated with sentinel events, adverse outcomes, and preventable medical errors, thereby compromising patient safety. Methods: The systematic review approach uses the Cochrane approach and journal sources from several databases including Scopus, Pubmed, BMJ, BMC, NCBI, ProQuest, Science Direct in the last 5 years. This article searched using keyword handover, electronis, SBAR and nursing care. Boolean operators in the search process using AND and OR. Data analysis of review using narrative analysis based on The Joanna Briggs Instritute for Critical Appraisal Tools. Results: Overall, the reviews consist of 15 articles. In this review, this electronic-based handover makes the delivery of information more structured, efficient and effective so that it can reduce ME (Medication Error), improve patient safety. Conclusions: The application of this electronic-based handover makes the delivery of information more effective, efficient and structured, to reduce sentinel events, medical errors, improve patient safety and improve the quality of nursing care.